The bioenergy potential of Natura 2000 – a synergy between climate change mitigation and biodiversity protection. Issue 9 (November 2016) - Van Meerbeek, Koenraad; Ottoy, Sam; de Andrés García, María; Muys, Bart; Hermy, Martin
Abstract : Climate change and biodiversity loss are two of the greatest challenges of the 21st century. To date, actions proposed by the international community to address these problems have largely been conducted in a piecemeal fashion. Conservation biologists advocate for low‐intensity management in temperate protected areas to maintain and restore biodiversity. Low‐input, high‐diversity biomass from such areas has been proposed as a promising alternative bioenergy feedstock. Here, we show that there is a vast unexploited biomass‐for‐bioenergy potential present in Natura 2000, the European nature conservation network. Spanning 7.5 million hectares (ha), non‐forest ecosystems within Natura 2000 have a biomass production of 17.9 teragrams (Tg) of dry matter annually. The conversion of this biomass to bioenergy will not lead to the displacement of food production systems, thereby avoiding 12.5 Tg of carbon dioxide equivalent greenhouse‐gas emissions and circumventing between 1.2 and 2.8 million ha of indirect land‐use change. The use of conservation biomass as bioenergy feedstock clearly offers the opportunity to reconcile biodiversity goals and climate‐change mitigation.